Making a difference: insights into effective HE progression practices in further education colleges. (1st June 2021) - Raven, Neil
Further education colleges (FECs) are significant providers of level 3 (higher education (HE) entry) courses. Yet, their role in preparing students, including those from widening participation backgrounds, for HE is often overlooked. Indeed, recent reports from the Office for Students have focused on the low HE progression rates returned by colleges. However, this focus overlooks the reality that students educated in FECs do progress and that in many instances colleges are very successful in this endeavour, given that those studying with them are more likely to come from educationally and economically disadvantaged backgrounds. This paper reports on the findings from a recent study that sought to identify the effective progression practices being pursued in two FECs. These include institution-wide activities as well as initiatives adopted at subject level. Whilst the latter have received less attention in the literature, the qualitative approach adopted in this study, which involved drawing on the insights of students as well as teaching staff, was able to detail the application of these subject-level practices. The article concludes by arguing for the wider adoption of subject-level as well as institution-wide practices, and for their potential to be recognised by those working in the HE sector more generally.